Hematologic abnormalities and pregnancy outcomes in pregnant women with COVID-19 - Mozer AbdAlraheem, Huda; AlJanabi, Rawaa D. M. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Since declaring coronavirus disease 19 as a pandemic by the World Health Organization, a great concern was directed toward pregnant women and their fetuses. Despite the substantial impact of COVID-19 disease on pregnancy, there is a scarcity of national researches discussing this important issue.          Objectives: To study the relationship between peripheral blood abnormalities and COVID-19 in pregnant women.Patients and methods: A case control study was conducted in the labour wards of Baghdad Teaching Hospital in the Medical complex / Baghdad /Iraq during the period from 1st of February till 31st of July, 2021. Fifty pregnant women diagnosed with COVID-19 disease were compared to 50 healthy pregnant women as controls. The pregnant women enrolled in the study were tested by COVID-19-Reverse transcription RT-PCR test upon admission to hospital. The confirmation of COVID-19 diagnosis was done according to the Iraqi guidelines approved by the Iraqi Ministry of Health.Results: Dyspnea was a significant clinical presentation of pregnant women with COVID-19 disease. Those women had abnormal white blood cell count, lymphocytopenia, high neutrophil to lymphocyte ratio, high platelets to lymphocyte ratio and mild to moderate anemia which were significant when compared to controls. The maternal and neonatal morbidity and mortality rates were higher among pregnant women with COVID-19 disease. Abnormalities in peripheral blood system parameters like lymphocyte count, neutrophils count, platelets count and hemoglobin level were predictors of maternal morbidity and mortality.Conclusions: The clinical presentations and hematological abnormalities are useful in the diagnosis of COVID-19 disease in pregnant women and may be used as predictors of maternal and neonatal morbidity and mortality.